2014
DOI: 10.3892/or.2014.3278
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 20 (HSPB6) regulates apoptosis in human hepatocellular carcinoma cells: Direct association with Bax

Abstract: Abstract.A small heat shock protein (HSP), HSP20 (HSPB6) is ubiquitously expressed in various tissues and has several functions. We previously reported that the expression of HSP20 protein in human hepatocellular carcinoma (HCC) cells is inversely proportional to the progression of HCC. In addition, we showed that HSP20 is associated with phosphoinositide 3-kinase (PI3K) and inhibits the proliferation of HCC cells via suppression of the AKT signaling pathway. However, the relationship between HSP20 and apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
(32 reference statements)
4
22
0
Order By: Relevance
“…Furthermore, in consistent with the previous result that HSPB6 inhibited LPS-induced NF-κB activation in cardiomyocytes, HSPB6 acts as a negative regulator of HCC via down-regulation of TNF-α-stimulated IKK/IκB/NF-κB pathway [86]. Additionally, HSPB6 directly associated with Bax, whereby it stimulated caspase cascade and induced apoptosis in HCC [11]. Collectively, HSPB6 might suppress HCC cell growth via both the downregulation of cell proliferation signals and the activation of apoptosis pathway.…”
Section: Role Of Hspb6 In Cancersupporting
confidence: 75%
“…Furthermore, in consistent with the previous result that HSPB6 inhibited LPS-induced NF-κB activation in cardiomyocytes, HSPB6 acts as a negative regulator of HCC via down-regulation of TNF-α-stimulated IKK/IκB/NF-κB pathway [86]. Additionally, HSPB6 directly associated with Bax, whereby it stimulated caspase cascade and induced apoptosis in HCC [11]. Collectively, HSPB6 might suppress HCC cell growth via both the downregulation of cell proliferation signals and the activation of apoptosis pathway.…”
Section: Role Of Hspb6 In Cancersupporting
confidence: 75%
“…We previously demonstrated that HSP20 decreases the proliferation and increases the apoptosis of HCC cells in the absence of TNF-a [12,14]. It is firmly established that the inflammatory signaling of TNF-a contributes to HCC development [3].…”
Section: Resultsmentioning
confidence: 97%
“…HSP20 directly interacts with PI3K and inhibits the PI3K activity in HCCs [13]. Moreover, we recently showed that HSP20 directly interacts with Bax and regulates apoptosis in HCC cells [14].…”
Section: Introductionmentioning
confidence: 98%
“…Among them, small Hsps (sHsps) are conserved and critical in stress tolerance among species. The sHsps (MW: ∼12–43 kDa) are identified by a highly conserved sequence (length: 80–100 amino acids) in the C‐terminal domain known as “α‐crystallin domain.” These types of Hsps possess major roles in differentiation, development, proteasomal degradation, autophagy, and apoptosis …”
Section: Introductionmentioning
confidence: 99%